Isolasi dan Skrining Aktivitas Antibakteri Fungi Tanah Muara Desa Katialada Gorontalo Lokasi Satu terhadap Staphylococcus aureus - Rohmatillah, Wilda Nur; Arifin, Muhammad Zainul; Tauladani, Saeful Akhmad; Muharam, Gani Asri; Asia, Asia; Pratoko, Dwi Koko; Nugraha, Ari Satia (Jurnal Kefarmasian Indonesia, 2022)
The emergence of antibiotic resistance becomes a barrier in controlling infectious diseases, so it is necessary to find new alternative antibiotics. This study aimed to explore the potential of estuarine soil fungals secondary metabolites isolated from Katialada Village Gorontalo Location One and test their antibacterial activity against Staphylococcus aureus. The antibacterial parameter observed was the percent inhibition of ethyl acetate extracts against Staphylococcus aureus. The estuarine soil samples were cultured in PDA media producing five single fungal isolates differentiated based on color morphology, texture, and shape coded IS2-BTG-4.1.1, IS2-BTG-4.1.2, IS1-BTG-4.2, IS2-BTG4.3.1, and IS2-BTG-4.3.2. Those five samples were fermented using PDB media and the fermented products were extracted with ethyl acetate. The extracts were screened for its compound using a TLC plate and antibacterial testing with a single concentration of 100 g/mL in the microdilution method. The screening results showed that the five ethyl acetate extracts contained terpenoid compounds and code IS2-BTG-4.3.2 also had alkaloids. Based on the antibacterial test results, the five ethyl acetate extracts had growth inhibitory activity on the Staphylococcus aureus, with the percentage showed by IS2-BTG-4.1.1 50,2% ± 14,8%, IS2-BTG-4.1.2 35,6% ± 12,9%, IS1-BTG-4.2 13,0% ± 7,3%, IS2-BTG-4.3.1 13,6% ± 6,0%, and IS2-BTG-4.3.2 by 12,4% ± 9,2%.